2019
DOI: 10.1088/1755-1315/394/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

The Floral Morphology and Anatomy of Kenanga (Cananga odorata (Lam.) Hook.f. & Thomson)

Abstract: Cananga odorata (Lam.) Hook.f. & Thomson is one of the essential oils producing plants that have many benefits for humans. However, there is little information about the floral morphology and anatomy of C. odorata. The aim of this study is examining the floral morphology and anatomy of C. odorata. The flower morphology (color, shape, and size of the flower) were observed at fresh mature flowers. While, the flower anatomy (pistil, stamen, and ovary) were observed at flower histological samples. The flower w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
1
3
0
2
Order By: Relevance
“…Numerous pointed stamens surround a group of separate pistils in the middle of the flower apex. This observation is consistent with the Cananga odorata flower morphology described by Parrotta and Nurhayani et al [1] [7].…”
Section: Flower Senescence +19supporting
confidence: 93%
See 1 more Smart Citation
“…Numerous pointed stamens surround a group of separate pistils in the middle of the flower apex. This observation is consistent with the Cananga odorata flower morphology described by Parrotta and Nurhayani et al [1] [7].…”
Section: Flower Senescence +19supporting
confidence: 93%
“…Meanwhile, flowers in the mature stages of development contain compounds that contribute to the flowers' aromatic scents, such as hydrocarbon, esters, and alcohol compounds [3]. Previous studies have observed the anatomy and morphology of a few different stages in the Cananga odorata flower development [7]. Another study has also observed the volatile organic compound emissions of different Cananga odorata flower development stages [3].…”
Section: Introductionmentioning
confidence: 99%
“…Cananga is a complete or perfect flower with petals, sepals, pistils, and stamens (Nurhayani et al 2019). The morphology of the two Cananga accessions observed showed differences in the leaf and stem characteristics, including leaf length, leaf width, petiole color, leaf's central vein color, and branch color.…”
Section: Discussionmentioning
confidence: 99%
“…Formula sediaan gel dibuat dengan memakai tiga variasi formula yang berbeda, dengan membedakan konsentrasi aloevera gel dengan aquadest dapat dilihat pada Tabel 1. Linalool, Germacrene-D, thymol, dan Limonene [7] Antiinflamasi dan antibakteri [8] 2…”
Section: Formulasi Sediaanunclassified